Current research trends on cosmetic microplastic pollution and its impacts on the ecosystem: A review. (1st March 2023) - Zhou, Yuwen; Ashokkumar, Veeramuthu; Amobonye, Ayodeji; Bhattacharjee, Gargi; Sirohi, Ranjna; Singh, Vijai; Flora, G.; Kumar, Vinay; Pillai, Santhosh; Zhang, Zengqiang; Awasthi, Mukesh Kumar
Abstract: Since the advent of microplastics, it has become a vital component, directly or indirectly, in our daily lives. With advancements in their use, microplastics have become an integral part of personal care, cosmetics, and cleaning products (PCCPs) and emerged as a domestic source of environmental pollution. Over the years, researchers have ascertained the harmful effects of microplastics on the environment. In this context, the assessment and monitoring of microplastics in PCCPs require considerable attention. In addition, it raises concern regarding the need to develop innovative, sustainable, and environmentally safe technologies to combat microplastic pollution. Therefore, this review is an endeavor to uncover the fate, route and degradation mechanism of cosmetic microplastics. In addition, the major technological advancement in cosmetic microplastic removal and the steps directed toward mitigating cosmetic microplastic pollution are also discussed. Graphical abstract: Image 1 Highlights: A detailed analysis on microplastic diversity and their cosmetic applications is discussed. Mechanisms involved in microplastic interaction with the environment is elaborated. Advanced biotechnological approaches to remove microplastic from the environment is discussed. Measures and controls to mitigate microplastic problems is discussed.